Sensitizers of the bacteriochlorin series: prospects of the usage in photodynamic therapy - А. M. Mironov; M. A. Grin (Тонкие химические технологии)
Materials concerning synthesis and chemical modification of the bacteriochlorophyll a for 10-15 years past were collected in this review. Effectiveness of the bacteriochlorin derivatives usage in photodynamic therapy was discussed. Directional chemical modifications, which lead to increasing of stability, improvement of photophysic properties and creation of water-soluble photosensitizers were report.